2017
DOI: 10.1111/jai.13307
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth and sex of the shanny, Lipophrys pholis (Linnaeus, 1758) (Teleostei, Blenniidae), from the NW coast of Portugal

Abstract: Summary Age, growth, sex and gonadal maturation of the shanny, Liphorys pholis, were determined in specimens caught in a rocky intertidal area in northern Portugal in order to provide essential ecological data on the species. This study represents the first available reference in the literature for L. pholis in a southern European location. Totals of 251 individuals (115 females, 99 males, 37 undetermined; total length: 30–172 mm) were collected seasonally (November 2013, March, June, and September 2014) in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Our results revealed that the breeding season for H. fissicornis spans five months as has been observed for some blennies that inhabit temperate zones, (e.g. Aidablennius sphinx, Carrassón & Bau, 2003, Lipophrys pholis, Shackley & King, 1977Carvalho et al, 2017 andIstiblennius enosimae, Sunobe et al, 1998).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results revealed that the breeding season for H. fissicornis spans five months as has been observed for some blennies that inhabit temperate zones, (e.g. Aidablennius sphinx, Carrassón & Bau, 2003, Lipophrys pholis, Shackley & King, 1977Carvalho et al, 2017 andIstiblennius enosimae, Sunobe et al, 1998).…”
Section: Discussionsupporting
confidence: 79%
“…Blennies live more than two years and sometimes up to 10 years (e.g. Lipophrys pholis; Dunne, 1977;Carvalho et al, 2017). The breeding season spans two months or more in temperate areas, with several spawning events (Qasim, 1956;Santos, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…For Japanese anchovy, a translucent band appears before the opaque band, and each opaque band was identified as an annulus ring [46]. The formation of annulus was proven to occur between May and September, with predominant occurrences in June and August, as indicated by marginal increment analysis [46][47][48][49]. This suggests that the timing of annual ring formation in anchovies corresponds with their spawning period, indicating a correlation between annulus formation and spawning events.…”
Section: Age Estimationmentioning
confidence: 96%